EVALUATING THE EFFECTIVENESS OF PATIENT EDUCATION TO COPE UP DEPRESSION IN MENOPAUSAL STAGE - SANKAR U, GANAPATHY; R, MONISHA; DOSS, CHRISTOPHER AMALRAJ VALLABA; RM, PALANIVEL (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The aim of the study was to assess the impact of education to combat depression in the menopausal stage. Methods: Twenty menopausal women, aged 50–55 years were recruited through convenience sampling procedure from Kancheepuram. Zung self-rating depression scale was administered to all the participants. Results: It revealed that there was a statistical difference in post-test after education on depression (t=13.413; p= 0.00) on menopausal women. Conclusion: Depression is the common psychological symptoms that affect the women at menopausal age. The severity is due to a lack of knowledge about the symptoms and a lack of awareness to cope with the psychological symptoms.